Горіх серцеподібний та г. айлантолистий (Juglans cordiformis Maхim., J. Ailantifolia Carr.) в умовах Лісостепу України: підсумки інтродукції та перспективи використання - Aboimova, A.M.; Levon, V.F.; Doroshenko, O.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective – to investigate the history of introduction of two species of nuts – Juglans cordiformis Maxim and J. ailantifolia Carr. in conditions of Forest-Steppe of Ukraine; to sum up the results of long-term purposeful introduction of these species in Forest-Steppe of Ukraine; to outline the prospects of their use. Material and methods. Subject of the research – perennial plantations of introduced species of the genus Juglans – J. cordiformis and J. ailantifolia. The studies were carried out according to the generally accepted methods in the collection plantings of the Department of dendrology of M.M. Gryshko National Botanical Garden of the NAS of Ukraine and in the urban plantings of Kyiv. Results. Wintering and drought tolerance J. cordiformis and J. ailantifolia was identified. Species J. ailantifolia less winter-hardy (34 points) and drought-resistant (23 points), compared with J. cordiformis (2 and 4 points, respectively). Analysis of the biochemical composition of the fruit confirmed the nutritional value of the nucleus J. cordiformis and J. ailantifolia. The fat content in the fruits of the studied species exceeds that in J. regia (62.8 and 61.4 % versus 58.4 %), the protein content in fruits of J. cordiformis is 43.1%, in fruits of J. ailantifolia – 41.2 %, which is three times more compared with J. regia. Conclusions. Winter and drought resistance of J. ailantifolia (23 points) was lower compared to J. cordiformis (4 points). The study of the content of anthocyanins in the shoots showed that during a decrease in air temperature, the content of anthocyanins increases sharply. In J. cordiformis, the content of anthocyanins in winter is 522.67 and in J. ailantifolia – 378.95 mg/100 g of dry matter, confirming the results of visual observations on the scale of winter hardiness of S.Ya. Sokolov. This figure in J. cordiformis is 2 points (freeze the ends of shoots last year vegetation), and in J. ailantifolia 34 points (freeze shoots last year for the entire length, and sometimes freeze shoots last two years). J. cordiformis and J. ailantifolia can be used in the garden and park economy of the Forest-Steppe of Ukraine as valuable food plants. J. ailantifolia is particularly in need of additional moisture in the dry period and in the use of agronomic measures to increase its winter hardiness.